2008
DOI: 10.1007/s00418-008-0445-4
|View full text |Cite
|
Sign up to set email alerts
|

Robust expression of Prominin-2 all along the adult male reproductive system and urinary bladder

Abstract: Although the male reproductive system seems to be enriched in transcripts encoding for both Prominin genes, little is known about their spatial distribution in distinct segments of this organ system. This is especially true for the less-characterized second Prominin paralogue, Prominin-2. The present study, therefore, mainly examines the expression of Prominin-2 in male mice and reveals the existence of some crucial diVerences in the tissue compartmentalization of the two Prominin paralogues in the testis, epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 58 publications
(89 reference statements)
1
26
0
Order By: Relevance
“…Although many tissuespeciWc progenitor cells express prominin-1 its expression is nevertheless not limited to those with stem cell properties. Indeed, prominin-1 has been detected on the apical (luminal) side of various developing and adult epithelia found in both, mouse and human organs (Corbeil et al 1998Fargeas et al 2004;Jászai et al 2007bJászai et al , 2008Lardon et al 2008;Karbanová et al 2008;reviewed in Fargeas et al 2006) including the kidney where it is expressed in proximal nephron tubules and parietal layer of the Bowman's capsule (Weigmann et al 1997;Florek et al 2005). Moreover, its expression is documented in nonepithelial cells such as photoreceptor and glial cells (Maw et al 2000;Yang et al 2008;Zacchigna et al 2009;Corbeil et al 2009).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although many tissuespeciWc progenitor cells express prominin-1 its expression is nevertheless not limited to those with stem cell properties. Indeed, prominin-1 has been detected on the apical (luminal) side of various developing and adult epithelia found in both, mouse and human organs (Corbeil et al 1998Fargeas et al 2004;Jászai et al 2007bJászai et al , 2008Lardon et al 2008;Karbanová et al 2008;reviewed in Fargeas et al 2006) including the kidney where it is expressed in proximal nephron tubules and parietal layer of the Bowman's capsule (Weigmann et al 1997;Florek et al 2005). Moreover, its expression is documented in nonepithelial cells such as photoreceptor and glial cells (Maw et al 2000;Yang et al 2008;Zacchigna et al 2009;Corbeil et al 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Tissue expression proWling of the two prominin transcripts have revealed their diVerential expression in many organ systems with, nevertheless, some degree of intersection in the genitourinary system (Fargeas et al 2003a;Florek et al 2005;Jászai et al 2008). Although the metanephros is particularly enriched in both prominin molecules only prominin-1 expression has been addressed at the immunohistochemical level in this organ (Weigmann et al 1997;Florek et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…A diVerential expression of prominin-1 and -2 was found in major cephalic exocrine glands of adult mice (Jaszai et al 2007). Prompted by the observation that the male reproductive system seems to be enriched in transcripts encoding for Prominin-1 and -2, Jaszai et al (2008) now investigated the spatial distribution of the proteins in distinct segments of this system in adult mice and in the human prostrate. By in situ hybridization, immunohistochemistry and Western blotting, the authors showed that prominin-2 was apparently expressed more abundantly than prominin-1 in all parts of the male murine gentiourinary tract analyzed, with the exception of the testis, and was the only prominin present in the urinary bladder epithelium.…”
Section: Male Reproductive Systemmentioning
confidence: 95%
“…Although prominin 1 is a well studied surface marker of somatic stem and progenitor cells (for review, see Jaszai et al 2008), the physiological function of the prominins is not clear. A diVerential expression of prominin-1 and -2 was found in major cephalic exocrine glands of adult mice (Jaszai et al 2007).…”
Section: Male Reproductive Systemmentioning
confidence: 99%
“…Jaszai et al (2008) characterized expression of prominin-1 and 2 along the adult male reproductive system and urinary bladder in male mice by ISH experiments. In contrast to tissues derived from epigonadal mesonephric tubules (i.e.…”
Section: Male Reproductive Systemmentioning
confidence: 99%